Quality, Trade, and Exchange Rate Pass-Through - Chen, Natalie (IMF Working Papers; Working Paper, 2014)
This paper investigates theoretically and empirically the heterogeneous response of exporters to real exchange rate fluctuations due to product quality. Our model shows that the elasticity of demand perceived by exporters decreases with a real depreciation and with quality, leading to more pricing-to-market and to a smaller response of export volumes to a real depreciation for higher quality goods. We test the proposed theory using a highly disaggregated Argentinean firm-level wine export dataset between 2002 and 2009 combined with experts wine rankings as a measure of quality. The model predictions find strong support in the data and the results are robust to different measures of quality, samples, specifications, and to the potential endogeneity of quality.